Primary cutaneous leiomyosarcoma: A rare malignant neoplasm - Akshay Bali; Ranjit Kangle; Maitrayee Roy; Bhagyashree Hungund (Wolters Kluwer Medknow Publications, 2013)
Primary cutaneous leiomyosarcoma (PCL) is an exceedingly uncommon malignant superficial soft tissue sarcoma with a predilection for middle-aged to elderly male. Morphologic differential diagnosis includes a host of other malignant spindle cell neoplasms, thereby necessitating the use of a panel of immunohistochemical markers to arrive at a definitive diagnosis. We report a case of PCL arising in the right leg of a 70-year-old male.